Actitudes y comportamientos alimentarios desordenados en mujeres universitarias: asociación con la actividad física, internalización de ideales de apariencia y autoobjetivación (Disordered eating attitudes and behaviors in college women: association with physical activity, inter-nalization of appearance ideals, and self-objectification) - Gonzaga, Isadora; Salvador Claumann, Gaia; Costa Miranda, Clair; Pelegrini, Andreia (Retos, 2024)
Este estudio verificó las asociaciones de actitudes y comportamientos alimentarios desordenados con la actividad física moderada y vigorosa, la internalización de los ideales de apariencia y la autoobjetivación en mujeres universitarias. Participaron 472 estudiantes brasileñas de 18 a 30 años (media 21.85 años; DE = 4.46). Las actitudes y comportamientos alimentarios se evaluaron mediante el Eating Attitudes Test. Los niveles de actividad física se evaluaron mediante el International Physical Activity Questionnaire (versión larga). La internalización de los ideales de apariencia se evaluó mediante el Sociocultural Attitudes Towards Appearance Questionnaire-4-Revised-Female. La autoobjetivación se evaluó mediante la Self-Objectification Beliefs and Behaviors Scale. Se realizaron los coeficientes de correlación de Spearman y la regresión lineal múltiple con el método paso a paso para examinar las relaciones entre las variables. Las actitudes y comportamientos alimentarios desordenados mostraron correlaciones significativas (p< 0.01) y positivas con todas las variables. En el análisis de regresión lineal múltiple, solo la internalización del ideal muscular no se asoció con el resultado. El modelo final explicó el 41,3% de la variación de las puntuaciones de la variable dependiente. Las mujeres universitarias pueden ser susceptibles a actitudes y comportamientos alimentarios desordenados, de acuerdo con el nível de actividad física, internalización del ideal de delgadez/baja grasa corporal y de atractivo general, y autoobjetivación.Palabras clave: Apariencia Física. Actividad Física; Conducta Alimentaria; Imagen Corporal. Mujeres.Abstract. This study aimed to examine associations of disordered eating attitudes and behaviors with moderate to vigorous physical activity, internalization of appearance ideals, and self-objectification in college women. Participants were 472 Brazilian college women, aged 18 to 30 years (mean 21.85 years; SD = 4.46). Disordered eating attitudes and behaviors were assessed using the Eating Attitudes Test. Physical activity levels were assessed using the International Physical Activity Questionnaire (long version). Internalization of appearance ideals was assessed using the Sociocultural Attitudes Towards Appearance Questionnaire-4-Revised-Female. Self-objectification was assessed using the Self-Objectification Beliefs and Behaviors Scale. Spearman's correlation coefficients and multiple linear regression were conducted to examine the associations between the variables under investigation. Disordered eating attitudes and behaviors showed significant (p< 0.01) and positive correlations with all independent variables. In the multiple linear regression analysis, only the internalization of the muscular ideal was not associated with the outcome. The final model explained 41.3% of the variation of the dependent variable scores. College women may be susceptible to disordered eating attitudes and behaviors, according to their levels of physical activity, internalization of the thin/low body fat ideal, internalization of the general attractiveness ideal, and self-objectification.Keywords: Physical Appearance. Exercise. Eating Behavior. Body Image. Women.